رؤية استشرافية حول شكل الحكومة العراقية المقبلة: فى ضوء نتائج الانتخابات البرلمانية 2018 م - Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي (Center for Research and knowledge networking | مركز البحوث والتواصل المعرفي, 2023)
The results of the parliamentary elections announced a major shift in the Iraqi arena that took place on 12 May 2018. This transformation focused on significant progress achieved by some political blocs and parties Some of which were in the middle of the list of political blocs and parties during the past years, including The bloc of the leader of the Sadrist movement, Muqtada al-Sadr, is an alliance, "Striving Towards Reform," and some of them were not A political bloc or party is present in the political arena, such as: “The Victory Coalition.” And in return for this The positive rise There was a significant decline of the political blocs and parties that led the Iraqi state during the two months The past ten years, and here we refer to the Dawa Party “State of Law Coalition,” which lost 71 seats Parliament from the 2014 elections, in which he won 96 seats, compared to 25 seats he won them in the 2018 elections. | أعلنت نتائج الانتخابات البرلمانية حدوث تحول كبير في الساحة العراقية التي جرت في 12 مايو عام 2018م. وهذا التحول تركز في تقدم كبير أحزرته بعض الكتل والأحزاب السياسة التي كان بعضها في وسط قائمة الكتل والأحزاب السياسية خلال السنوات الماضية، ومنها كتلة زعيم التيار الصدري مقتدى الصدر تحالف «سائرون نحو الإصلاح،» وبعضها لم يكن موجوداً ً على الساحة السياسية كتلة أو حزباً سياساً، مثل: «ائتلاف النصر.» وفي مقابل هذا الصعود الإيجابي حدث تراجع كبير لكتل وأحزاب سياسية قادت الدولة العراقية خلال الاثني عشر عاماً الماضية، وهنا نشير إلى حزب الدعوة «تحالف دولة القانون،» الذي فقد 71مقعداً برلمانياً من انتخابات عام 2014م، التي حصل فيها على 96مقعداً، في مقابل 25مقعداً حصل عليها في انتخابات عام 2018م.